Capturing interpersonal coordination processes in association football: from dyads to collectives - Lima Duarte, R. F. (2012)
The purpose of this thesis was to investigate how football performers coordinate their behaviours in different levels of social organisation. We began with a position paper proposing the re-conceptualisation of sport teams as functional integrated superorganisms to frame a deeper understanding of the interpersonal coordination processes emerging between team players. Time-motion analysis procedures and innovative tools were developed and presented in order to capture the superorganismic properties of sports teams and the interpersonal coordination tendencies developed by players. These tendencies were captured and analysed in representative 1vs1 and 3vs3 sub-phases, as well as in the 11-a-side game format. Data showed higher levels of variability at the individual level compared to the team level. This finding suggested that micro-variability may contribute to stabilise the behavioural dynamics at the collective level. Moreover, the specificities of the interpersonal coordination tendencies displayed within attacking-defending dyads demonstrated to have influenced the performance outcome. Attacking players tend to succeed when they were more synchronised in space and time with the defenders, and their interaction were more unpredictable/irregular. Besides, the time-evolving dynamics of the collective behaviours (i.e., at 11-a-side level) during competitive football performance indicated a tendency for an increase in the predictability (i.e., more regularity). These data were interpreted as evidencing co-adaptation processes between opponent players, which suggest that team players may shift from prevalent explorative and irregular behaviours to more predictable behaviours emerging due changes in their functional movement possibilities. However, some game events such as goals scored, halftime and stoppages in play seemed to break this continuum and acted as relevant performance constraints.